The ideological burden in the tools of bibliographical organization - Meneses Tello, Felipe (Revista General de Información y Documentación, 2013)
The author analyzes the heavy ideological burden that lists of subject headings and classification schemes have. These are the main tools for bibliographic organization in the world of libraries. Also, in virtue of the conceptual similarities and differences around bibliographic organization in the fields of library science and documentation, a study of the terminology of this latter discipline is taken. The work is divided into two parts: 1] the subject cataloging universe and 2] the sphere of bibliographic classification. In the first part the author discusses the cataloging of African-American literature; the alternative cataloging of Sanford Berman; cataloging in the ideological construction of social inequities; alternative cataloging as an option including terms, and cataloging as a political weapon in situations of ideological rivalry. In the second part he discusses topics such as: the ideological mission of classification systems in the capitalist context, the ideological essence of bibliographic classification in the socialist environment; class society as an ideological element at the level of classification and the ideological-class struggle-classification connection as political relationship. He concludes that the ideological burden of subject headings and classification schemes is determined by the social relations of production that predominate in the social and political structure of the state.